The effective utilization of internet bandwidth in organizational demand services and applications - Adamu Abubakar,; Wan Nurul Izza Wan Husin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research evaluates the sustainable utilization of Internet bandwidth usage and proposes a framework for organizational Internet Bandwidth demand service. The study highlighted the lack of an understanding of how much internet bandwidth is required for business and individual use and to what extent individual users must be familiar with it. This is crucial because it will enable a smooth data transmission flow back and forward in an organizational network. That is why this study seeks to (1) measure the relationship between organizational learning and effective utilization of internet bandwidth; (2) assess the relationship between organizational learning and organizational performance, and (3) investigate the mediating impact of effective utilization of internet bandwidth in influencing the relationship between organizational learning and organizational performance. We adopted the quantitative research methodology, and a reasonable sample population (n=318) was selected from those Malaysian business firms that use Internet bandwidth. Structural equation modeling (SEM) was utilized to test the relationship among study variables. The finding indicates that; organizational learning is of critical importance in the effective utilization of Internet bandwidth. However, effective bandwidth utilization does not mediate the relationship between organizational learning and performance. This result is interpreted that learning how to use Internet bandwidth improves individual usage and better decision-making in choosing an organization's Internet bandwidth-demand services and applications. Still, it does not significantly increase operational and financial performance.